2021
DOI: 10.3389/fpls.2021.705834
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cis-Regulatory Elements for Rice Grain Quality Improvement

Abstract: Rice is the most important source of food worldwide, providing energy, and nutrition for more than half of the population worldwide. Rice grain quality is a complex trait that is affected by several factors, such as the genotype and environment, and is a major target for rice breeders. Cis-regulatory elements (CREs) are the regions of non-coding DNA, which play a critical role in gene expression regulation. Compared with gene knockout, CRE modifications can fine-tune the expression levels of target genes. Geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…The mutation in abscisic acid response elements not only lessens the ABA response but also can inhibit the leucine zipper proteins binding that might affect many biological responses [60]. The Ry and gibberellin elements are investigated grain quality in rice [61]. The occurrence of these cis-regulatory elements provided evidence of BnSDGs's role in growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…The mutation in abscisic acid response elements not only lessens the ABA response but also can inhibit the leucine zipper proteins binding that might affect many biological responses [60]. The Ry and gibberellin elements are investigated grain quality in rice [61]. The occurrence of these cis-regulatory elements provided evidence of BnSDGs's role in growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to improve crop characteristics, many genes that regulate essential traits must have a high translation rate rather than functional loss or reduction ( Reis et al., 2020 ). Recently, the modification of cis-regulatory elements has been shown to be a practical approach for fine-tuning the expression levels of target genes and is therefore a promising strategy for rice ECQ improvement ( Ding et al., 2021 ).…”
Section: Modern Molecular Breeding Strategies For Rice Ecq Improvementmentioning
confidence: 99%
“…Although the most frequent application of CRISPR/Cas9 is to create null alleles by targeting the coding sequences, loss-offunction mutations in coding regions may result in pleiotropic or deleterious effects (Li et al, 2020a;Hendelman et al, 2021). Numerous researches in both animals and plants have revealed that many genetic changes driving evolution, domestication, and breeding occurred in cis-regulatory regions, including upstream, introns, and downstream regions of genes (Wang et al, 2014;Ding et al, 2021). Compared with coding region mutations, cis-regulated region editing is more likely to induce small phenotypic changes by modifying the level, timing, or space of gene expression, which benefit crop improvement.…”
Section: Expression Regulationmentioning
confidence: 99%